Warmth and Demand: The Relation Between Students' Perceptions of the Classroom Environment and Achievement Growth. Issue 4 (9th December 2016) - Sandilos, Lia E.; Rimm‐Kaufman, Sara E.; Cohen, Julia J.
Abstract : Theory suggests that African American students benefit from warm and demanding teachers. This study examines the relation between students' perceptions of 634 teachers' warm demander characteristics and achievement growth in fourth and fifth grades ( M student age = 9–11.5 years). Analyses explored whether relations were moderated by the proportion of African American students in the classroom or the ethnic match or mismatch between African American students and their teachers. Results indicated that students' perceptions of teachers' demand (challenge and control) related to student achievement growth. Findings showed a stronger relation between challenge and academic growth in classrooms with more African American students, but no significant findings were identified for ethnic match or mismatch.